Fiten ve Melâhim Edebiyatı - Sarp, Refiye Öznil (My University, 2010)
ten, Melahim, Hadis Edebiyatı ÖZET FİTEN VE MELAHİM EDEBİYATI Fiten ve Melahim Edebiyatı, Hz. Peygamber’in yakın ve uzak gelecekle ilgili verdiği haberlerin, meydana gelecek fetihler ve savaşlarla ilgili rivâyetlerin yer aldığı eserleri ifade etmektedir. Bu çalışma, konu ile alakalı hicri ilk üç asırda yazılmış eserlerin ilgili bölümleri ile müstakil çalışmaları konu almaktadır. Bu eserlerin konu başlıklarını ve muhtevasını sıralayıp değerlendirmesini yapmayı hedeflemektedir. Degree Awarded and Date: Master- November 2010 tan, al-Malahim, Hadith Literature

al-FITAN AND al-MALAHIM LITERATURE al-Fitan and al-Malahim literature expresses the books include news which Prophet (pbuh) declares about near and far future and narratives related to the conquests and wars that will happen. This study analyzes the related parts of the books that written in the first three century of hicra and separate books. It aims to count the subject titles and content of these books and to evaluate them.
Keywords: Hadis; İslam Dini